On the identity of some poorly known species of the genus Endonura Cassagnau, 1979 (Collembola, Neanuridae, Neanurinae) - Smolis, Adrian (Zootaxa, 2016)
New data on little known species of the genus Endonura are provided. E. transcaucasica (Stach, 1951), from Georgia, is redescribed in details and its lectotype is designated. E. centaurea (Cassagnau & Péja, 1979) and E. deharvengi (Cassagnau & Péja, 1979), both described from Greece, are redescribed and illustrated based on type material for the first time. Redescription of E. caeca (Gisin, 1963), a taxon known only from the type locality in Bosnia and Herzegovina, is given based on holotype.